Impacto de la educación en economía solidaria sobre acciones solidarias de egresados de la Facultad de Odontología de la Universidad Cooperativa de Colombia, sede Pasto (2012)
Introduction: This article pre.sents rhe research project entitled "Impact of Solidarity Economy Education on Solidariry Actions by Alumni of the Univers1dad Cooperativa de Colombia Dental School in Pasto" which was completed in 201 hy the Dental Research Group (Grupo de lnvestigacilines en Odonmlogfa, GIOll) at the Pastn campus ot the Universidad Cnoperativa de Colt)ml:,ia. Methods: A cohort of demises from that university was compared with ,lther Dental School alumni from 2002 to 2010. Information on dentists' demographic and socio-economic variables, leadership skills, participation in ,nlidarity economy organizations and enterprise creation was ,lbtamed by a self-.idmini,tcrcJ questionnaire. The statistical analyses were perfom1ed using sr,, 17 version. Results: This study shows that therewere no stauscical differences between the two cohorts accordmg to demographic .,nd ,ncio-economic variables. 7.7% had leadership skill,. The entire cohort pointed to meaninr: (21.2°0) and membership (2 \2°,,) as principal Personal Leadership Scale components. 06.7% of dentists i:raduaced from our umver,ity participated in s.)lidarity economy organizations, while a similar percentage oi alumm frnm other dental schools were involved in enterprise creation. Conclusions: The results of chis research indicate that it is imperative rhat chis uni\•ersity design strategies to increase leadership ,kills and improve sc>liJarity economy courses in the ,idontology curriculum.